HARAPAN PASAR TERHADAP LULUSAN UNIVERSITAS - fatik Rahayu (Universitas Trisakti, 2005)
Some surveys, reveals that Quality Management can help organization to improve customers satisfaction. This study examines customers' need and expectations of Universities' graduates. The questionare were sent to human resources' managers in Jakarta.